Comparative transcriptomic analysis of plum fruit treated with 1-MCP - Ziosi, Vanina; Costa, Guglielmo; Jajo, Aiman; McGlasson, Barry; Holford, Paul; Jones, Mark R.; Golding, John; Angelo, Ramina; Tonutti, Pietro; Bonghi, Claudio; Manganaris, George A. (My University, 2009)
Microarray technology has allowed the large scale transcriptomic analysis of fruit ripening. The μPEACH1.0 microarray containing 4,806 probes corresponding to genes expressed in peach fruit tissues has been used in a heterologous fashion in two studies of plums ripening behavior. Gene expression of different cultivars of plums treated with the ethylene antagonist, 1-methylcyclopropene (1-MCP) and stored for short periods at room temperature or for longer periods of cold storage was examined. In the first study, mature fruit of a suppressed ethylene climacteric cultivar 'Shiro' and a cultivar characterized by a typical increase of ethylene production during ripening ('Santa Rosa') were harvested and incubated for 24h in air (control) or 1-MCP and allowed to ripen at room temperature. Different levels of transcripts of genes implicated in cell wall metabolism, hormone (ethylene and auxin) regulation, stress and defense, and in the transcription/translation machinery, as well as others involved with ripening were identified. In the second study, the effects of 1-MCP on gene expression in relation to the development of chilling injury (CI) in the climacteric cultivars 'Ruby Red' (RR) and 'October Sun' (OS) and 'Zee Lady' peaches (ZP) were analyzed. The fruit were treated for 24h at room temperature with 1-MCP prior to storage at 0°C. For RR, there was no significant effect of 1-MCP on the level of CI symptoms, while 1-MCP significantly reduced CI symptoms in OS fruit and an increase of CI in treated ZP fruit. Microarray analysis showed that immediately following treatment, 186, 134 and 56 genes were differentially expressed between the control and 1-MCP-treated fruit of these cultivars, respectively: after 4 weeks cold storage, 311, 52 and 224 genes for RR, OS and ZP, respectively, were differentially expressed between control and treated fruit. Thus, for OS, the number of differentially expressed genes reduced during storage while the number increased in RR and ZP. Comparisons of the data suggest that the transcript profile is altered by 1-MCP more in plums than peaches. These studies, carried out within an international collaborative network, will increase our understanding of the regulation of pathways involved in plum fruit ripening and in metabolic processes related to storage and shelf life
Keywords: Ethylene; Fruit--Ripening; Peach; Plum; Prunus